Improving Outcomes for Infants with Single Ventricle Physiology through Standardized Feeding during the Interstage - Cindy Weston; S. Adil Husain; Christopher L. Curzon; Steve Neish; Gemma T. Kennedy; Krista Bonagurio; Kevin Gosselin (Nursing Research and Practice)
Congenital heart disease is identified as the most common birth defect with single ventricle physiology carrying the highest mortality. Staged surgical palliation is required for treatment, with mortality historically as high as 22% in the four- to six-month period from the first- to second-stage surgical palliation, known as the interstage. A standardized postoperative feeding approach was implemented through an evidence-based protocol, parent engagement, and interprofessional team rounds. Five infants with single ventricle physiology preprotocol were compared with five infants who received the standardized feeding approach. Mann-Whitney U tests were conducted to evaluate the hypotheses that infants in the intervention condition would consume more calories and have a positive change in weight-to-age z-score (WAZ) and shorter length of stay (LOS) following the first and second surgeries compared to infants in the control condition. After the protocol, the change in WAZ during the interstage increased by virtually one standard deviation from 0.05 to 0.91. Median LOS dropped 32% after the first surgery and 43% after the second surgery. Since first- and second-stage palliative surgeries occur within the same year of life, this represents savings of $500,000 to $800,000 per year in a 10-infant model. The standardized feeding approach improved growth in single ventricle infants while concurrently lowering hospital costs.